1992
DOI: 10.1063/1.350667
|View full text |Cite
|
Sign up to set email alerts
|

The inductance of the discharge in a spark gap

Abstract: The inductance of an arc discharge has been modeled and a mathematical formula given for the arc inductance in terms of its geometrical dimensions. This formula agrees with the experimental results and is used to determine the arc-channel radius. Inductance measurements have been taken for various values of pressure, interelectrode distance and applied voltage in a triggered spark gap. The dependence of inductance upon these parameters has been explained through the existing variations of the arc-channel cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
2

Year Published

1996
1996
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(20 citation statements)
references
References 6 publications
2
16
0
2
Order By: Relevance
“…The temporal variation of the current and the voltage indicates that the discharge behaves like a spark discharge [31][32][33][34][35][36].…”
Section: Capacitive Power Supplymentioning
confidence: 99%
“…The temporal variation of the current and the voltage indicates that the discharge behaves like a spark discharge [31][32][33][34][35][36].…”
Section: Capacitive Power Supplymentioning
confidence: 99%
“…25 The spark discharge was shown to have an inductive component on the order of 10 nH. 26 Since this value is more than 2 orders of magnitude lower than the total inductance of our discharge circuit, the inductance of the discharge gap was neglected with respect to the total inductance of our discharge circuit. More complete electrical models take into account the capacitance of the electrodes and the inductance of the plasma, along with the capacitance, resistance, and inductance of the used probes.…”
Section: A Electrical Resultsmentioning
confidence: 99%
“…For continuous operation it is preferred to use a large air-flow rate, to remove the evaporated electrode material from the gap, preventing it from accumulating inside the switch or on the insulators. Furthermore, according to Persephonis et al, 13 although the inductance of the switch decreases for decreasing gap distance and increasing gas pressure, for a fixed gap distance an increase in pressure results in an increase in inductance.…”
Section: A Operating Regimes For Stable Trigger Performancementioning
confidence: 89%
“…In Ref. 13 it was shown that by decreasing the gap distance, the inductance of the switch decreases. To prevent pre-firing of the switch when the distance is reduced, the spark-gap switch has to be pressurized.…”
Section: Spark-gap Switch Designmentioning
confidence: 99%